2018
DOI: 10.3390/brainsci8110202
|View full text |Cite
|
Sign up to set email alerts
|

New Hope in Brain Glioma Surgery: The Role of Intraoperative Ultrasound. A Review

Abstract: Maximal safe resection represents the gold standard for surgery of malignant brain tumors. As regards gross-total resection, accurate localization and precise delineation of the tumor margins are required. Intraoperative diagnostic imaging (Intra-Operative Magnetic Resonance-IOMR, Intra-Operative Computed Tomography-IOCT, Intra-Operative Ultrasound-IOUS) and dyes (fluorescence) have become relevant in brain tumor surgery, allowing for a more radical and safer tumor resection. IOUS guidance for brain tumor surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…In particular, in benign histopathologic entities such as pilocytic astrocytoma, complete removal can be curative. 4 Established tools to achieve high rates of gross total resection (GTR) in glioma surgery are intraoperative ultrasound, 5 intraoperative magnetic resonance imaging (iMRI), [6][7][8] and 5-aminolevulinic acid (5-ALA). 9 In the typical pediatric histopathologic entities, poorer results of 5-ALA are reported.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in benign histopathologic entities such as pilocytic astrocytoma, complete removal can be curative. 4 Established tools to achieve high rates of gross total resection (GTR) in glioma surgery are intraoperative ultrasound, 5 intraoperative magnetic resonance imaging (iMRI), [6][7][8] and 5-aminolevulinic acid (5-ALA). 9 In the typical pediatric histopathologic entities, poorer results of 5-ALA are reported.…”
Section: Introductionmentioning
confidence: 99%
“…iMRI with integrated functional neuronavigation is commonly used to achieve better visualization of residual tumor volume and to reassess neuronavigation during surgical manipulation to overcome brain shift ( 60 , 67 ). As an adjunct, IOUS with our without contrast enhancement (CEUS) is a valuable tools to distinguish tumoral tissue from normal brain parenchyma; notably, IOUS is more accessible than iMRI and it immediately allows a real-time visualization of tumoral tissue during surgical manipulation ( 68 ). As regards fluorescent dyes, 5-ALA is specifically accumulated by glioma cells and it is enlightened by intraoperative source of blue-light ( 10 , 52 , 53 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…From the interaction between ultrasound beams and cells, four main physical phenomena occur reflection, refraction, diffusion, absorption. In the last few decades, many studies showed how ultrasounds could be used not only for clinical or intraoperative diagnostic purposes also for therapeutics [ 1 ].…”
Section: Introductionmentioning
confidence: 99%